Verbalizer-visualizer preferences of engineering students: Validity and reliability - Kurniawan, Citra; Setyosari, Punaji; Kamdi, Waras; Ulfa, Saida (Research and Social Study Institute, 2023)
Learning content has several forms of presentation, both visual and verbal, but students have different characteristics in processing information depending on their learning preferences. Some students have difficulty processing information without knowing what to do. This happens because students do not yet understand the characteristics of their learning styles. This research aims to study the VVQ instrument used by engineering students by measuring the validity and reliability of the VVQ instrument used. This research uses a statistical quantitative method approach to measure the validity and reliability of the instrument. The instrument development process goes through three stages: analysis and formulation of a literature review, development of the VVQ instrument, and measurement of the validity and reliability of the VVQ instrument. Development of question items based on pre-arranged and customized content categories. The development of VVQ in this study shows the validity value of rcount > rtable, rcount > 0.1966 for each item, and the Person Moment (rxy) correlation is moderate (0.40 < rxy < 0.60) and high (0.60 < rxy < 0.80 ). This research instrument is reliable because the data shows Cronbach's Alpha value rcount > rtable; 0.817 > 0.6319, and the difficulty level is proportional (medium and high). The VVQ instrument achieves validity and reliability based on the analysis items that have been measured. The implications of this research have a significant impact on adjusting learning content to be more personalized based on student learning preferences.